Food availability modulates temperature‐dependent effects on growth, reproduction, and survival in Daphnia magna. Issue 2 (27th December 2019) - Betini, Gustavo S.; Wang, Xueqi; Avgar, Tal; Guzzo, Matthew M.; Fryxell, John M.
Abstract: Reduced body size and accelerated life cycle due to warming are considered major ecological responses to climate change with fitness costs at the individual level. Surprisingly, we know little about how relevant ecological factors can alter these life history trade‐offs and their consequences for individual fitness. Here, we show that food modulates temperature‐dependent effects on body size in the water flea Daphnia magna and interacts with temperature to affect life history parameters. We exposed 412 individuals to a factorial manipulation of food abundance and temperature, tracked each reproductive event, and took daily measurements of body size from each individual. High temperature caused a reduction in maximum body size in both food treatments, but this effect was mediated by food abundance, such that low food conditions resulted in a reduction of 20% in maximum body size, compared with a reduction of 4% under high food conditions. High temperature resulted in an accelerated life cycle, with pronounced fitness cost at low levels of food where only a few individuals produced a clutch. These results suggest that the mechanisms affecting the trade‐off between fast growth and final body size are food‐dependent, and that the combination of low levels of food and high temperature could potentially threaten viability of ectotherms. Abstract : Food modulates temperature‐dependent effects on body size in the water flea Daphnia magna and interacts with temperature to affect life history parameters.